The Legal Consequences of the Forgive Deed Bringed by the Prisoner to the Notary - Reza Meilanda Lesmana; Dika Sidataufa Aryatama (Khazanah Hukum, 2022)
Notaries as one of the public officials who are vulnerable to disputes in the agrarian sector as a consequence of negligence in carrying out their duties and authorities.  This research uses the method of juridical analysis of the norms and legal customs that exist in the community  public and analytical descriptive of the responsibilities of a notary and court decisions.  The results of the study indicate that there is negligence and unlawful behavior carried out by both an appearer and the notary himself.  This can be seen in the Decision of the Supreme Court of the Republic of Indonesia, Supreme Court Decision No. 185 PK/Pid/2010, the Notary was sentenced based on Article 263 paragraph (1) of the Criminal Code (KUHP) Juncto Article 55 paragraph (1) to the- 1 The Criminal Code (KUHP), which imposes penalties on notaries for falsifying documents.  In this case, the Notary as a State official and serving as law enforcement is dealing with the law for actions that he did not commit, as a result of the parties submitting the deed by bringing fake letters or documents.  While the Notary argued that his party did not know that the documents received from his client were fake.  So that, there is a void of legal norms in the Notary Position Act relating to legal protection and the responsibility of the Notary in making the deed based on data and information falsified by the parties. Therefore, it is necessary to have justice and legal certainty that can solve these problems.